2007
DOI: 10.1007/s00268-007-9013-7
|View full text |Cite
|
Sign up to set email alerts
|

Role Of Ultrasonography in Predicting Malignancy in Patients with Thyroid Nodules

Abstract: The use of ultrasonography (USG) has become an essential part of endocrine surgical practice. We evaluated the value of USG in predicting malignancy of thyroid nodules. The accuracy of USG in 857 patients who underwent fine-needle aspiration (FNA) with or without surgery was analyzed in a prospective setting. The diagnostic accuracy of USG was compared to that of FNA and of combined models in 153 operated patients. The malignancy-predicting value of USG in follicular neoplasms and its relation to nodule size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 26 publications
(27 reference statements)
1
39
0
1
Order By: Relevance
“…When the results of FNAB and US indicated that the lesion was benign, we chose clinical follow-up rather than surgery. Focal thyroid nodules that had not been operated on were excluded to analyze the false-negative rate, resulting in a relatively low negative predictive value compared with other studies [6, [47][48][49]. Therefore, the false-negative rate of 5.8% may not be an accurate measurement.…”
Section: Discussionmentioning
confidence: 96%
“…When the results of FNAB and US indicated that the lesion was benign, we chose clinical follow-up rather than surgery. Focal thyroid nodules that had not been operated on were excluded to analyze the false-negative rate, resulting in a relatively low negative predictive value compared with other studies [6, [47][48][49]. Therefore, the false-negative rate of 5.8% may not be an accurate measurement.…”
Section: Discussionmentioning
confidence: 96%
“…In Turkey, the prevalence of thyroid nodules was reported as 33% in a study which included 1,831 subjects screened for thyroid nodules (7). The (10). In the present study, we correlated the findings of ultrasonography, scintigraphy, FNA and thyroidectomy in patients with nodular thyroid disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, performing FNAB on every thyroid nodule detected by ultrasound is not cost-effective due to the high prevalence of nodules. Ultrasound is the most sensitive test available to detect thyroid lesions (Moon H.C. et al, 2007) and may be used to further characterize thyroid nodules, providing an assessment of risk of malignancy, and thereby narrowing down those nodules which require FNAB. Numerous studies have investigated the sonographic features of nodules as predictors of malignancy (Reading et al, 2005;Hoang et al, 2007;Moon W.J.…”
Section: Introductionmentioning
confidence: 99%